Rapid Neurodevelopmental Assessment (RNDA) : An Important Tool for Assessment of Psychomotor Development in Children with Perinatal Events - Das, Dhananjoy; Sultana, Kawsar; Ali, Golam Mohammed Tayeb; Barua, Tanuka; Arzu, Mahmood A Chowdhury (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Infants with various perinatal events are at risks for long term neurodevelopmental impairments. Neurodevelopmental assessment at early life has been considered as a valuable tool for prediction of neurodevelopmental outcomes in this population. This present study aimed to identify the neurodevelopmental impairments in high risk children by Rapid Neurodevelopment Assessment (RNDA) Materials and methods : This was a cross sectional study conducted in the Autism and Child Development Centre of Chattogram Maa Shishu-O-General Hospital during the period of 0ctober to December 2018. Babies aged 0 -2 years with different perinatal events like prematurity, birth asphyxia, neonatal jaundice, and without any adverse event; that attended RNDA clinic underwent Rapid Neurodevelopmental Assessment (RNDA) to find at risk children for long term neurodevelopmental impairments. Results: Among the 50 study subjects,Perinatal asphyxia was found in 41(82%). 26(52%) had history of IUGR, 22(44%) had Preterm delivery and 25(50%) had history of Neonatal convulsion. History of neonatal jaundice was found in 14(28%) cases. 5(10%) children did not have any perinatal event. The Mean ± SD age of study subjects was 7.38±7.31month. Severe impairment in gross motor and fine motor function were found in 25(50%) and 24(48%) respondents respectively. Vision was severely impaired in 10(20%) cases. Severe cognition and behavior impairment were found in 8(16%) and 3(6%) cases accordingly. Severe hearing and speech impairment were found in 2(4%) & 10(20%) cases respectively. Severe seizure was found in 19(39%) cases. Study subjects with the history of delayed cry or Perinatal asphyxia had significantly decreased fine motor skills. Children born with IUGR had significant gross motor and fine motor skill impairment. Significant speech & cognitive impairment were observed in children with neonatal jaundice. Seizure was found significant in study subjects with a history of neonatal convulsion. Conclusion: Rapid Neurodevelopment Assessment (RNDA) plays an important role for early identification of neurodevelopmental impairments of high-risk infants and thus screening for these can promote early therapeutic intervention and subsequent follow up, leading to better outcome. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 16-21